Delineating Masculinity Belief in Guy de Maupassant's Three Short Stories - Kasih, Elisabeth Ngestirosa Endang Woro; Husna, Mufaza; Mulia, Muhammad Rizki; Fithratullah, Muhammad (Journal of Feminism and Gender Studies, 2022)
This study aims to delineate masculinity issues in Guy Maupassant's Father Milon, A Duel and The Coloniel's Ideas short stories. This study sees that the practice of masculinity in the society legitimizes the dominant position of men and justifies the subordination of the male and female population in general and other marginalized ways of being male. This study employed Stuart Hall's representation and Gramsci's hegemony theories to delineate masculinity in Maupassants' three short stories. The qualitative descriptive method was applied as the data were in the form of narration and dialogues. The short stories revealed the dominant position of men in society that justifies the subordination of the male and female population in general. Finally, with the creation of different male characters with various degree of masculine nature, Guy Maupassant in Father Milon, A Duel and The Coloniel's Ideas tries to balance the male character he creates. Maupassant is just trying to paint pictures of different kinds the man seen in society, therefore, confirms the verisimilitude between characters in literary works and real-life characters.